2007
DOI: 10.1021/tx700093j
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Particles from the Paris Subway System

Abstract: Particulate matter (PM) from atmospheric pollution can easily deposit in the lungs and induce recruitment of inflammatory cells, a source of inflammatory cytokines, oxidants, and matrix metalloproteases (MMPs), which are important players in lung structural homeostasis. In many large cities, the subway system is a potent source of PM emission, but little is known about the biological effects of PM from this source. We performed a comprehensive study to evaluate the biological effects of PM sampled at two sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 40 publications
1
52
1
2
Order By: Relevance
“…In an in vivo study C57Bl/6 mice were exposed to different types of particles (100 mg), such as subway PM -10 particles and diesel exhaust particles, by intratracheal administration. Signs of inflammatory response were observed in BALF 8 h after exposure with an increased number of neutrophils (subway and diesel exhaust particles) as well as inflammatory mediators TNF-a and macrophage inflammatory protein (subway) [24]. The discrepancies with our results could be explained by the exposure methods used, intratracheal administration versus normal inhalation of larger particles, which target different lung compartments.…”
Section: Discussioncontrasting
confidence: 96%
“…In an in vivo study C57Bl/6 mice were exposed to different types of particles (100 mg), such as subway PM -10 particles and diesel exhaust particles, by intratracheal administration. Signs of inflammatory response were observed in BALF 8 h after exposure with an increased number of neutrophils (subway and diesel exhaust particles) as well as inflammatory mediators TNF-a and macrophage inflammatory protein (subway) [24]. The discrepancies with our results could be explained by the exposure methods used, intratracheal administration versus normal inhalation of larger particles, which target different lung compartments.…”
Section: Discussioncontrasting
confidence: 96%
“…However, the effects of subway particles in the respiratory system are poorly known. In order to examine this issue, BACHOUAL et al [78] exposed murine macrophages (RAW 264.7 cell line) and C57BL/6 mice to f10 mg?cm -2 and 100 mg, respectively, of subway particulate matter or ''reference'' materials (titanium dioxide (TiO 2 ), carbon black [79] and DEPs) over 24 h. They showed that noncytotoxic concentrations of subway particulate matter, but not of the other particles, induced a three-fold increased expression of MMP-12 mRNA both in vitro and in vivo (a transient increase in the latter). This was accompanied by a parallel increase in markers of oxidative stress (haem oxygenase-1 expression) and inflammation (tumour necrosis factor-a and MIP-2 production).…”
Section: Subway Particlesmentioning
confidence: 99%
“…Several studies concerning the air quality in subway systems worldwide have been conducted, focussing mainly on the concentrations of particulate matter (PM) (Martins et al, 2015 and references therein), as the exposure to PM can be related to the occurrence of adverse health effects such as respiratory and cardiovascular diseases (e.g. Pope et al, 2004), and the subway emissions have been shown to contribute to personal exposure to PM (Bachoual et al, 2007;Bigert et al, 2008;Minguill on et al, 2012). However, other authors such as Gustavsson et al (2008) found no increased lung cancer incidence among the subway drivers in Stockholm, and Seaton et al (2005) stated that those principally at risk from dust inhalation by working or travelling in the London Underground should not be seriously concerned.…”
Section: Introductionmentioning
confidence: 99%